OPTIMIZATION DIABETIC POLYNEUROPATHY PATIENTS MANAGEMENT USING A MULTIDISCIPLINARY APPROACH - V. A. Parfenov; V. A. Golovacheva; V. V. Fadeev; A. Y. Volovik; A. A. Golovacheva (Медицинский совет, 2017)
Introduction. The multidisciplinary approach, including pharmacological therapy, educational therapy, cognitive-behavioral therapy (CBT) has the leading role in management of patients with diabetic polyneuropathy (DPN). There is no domestic experience in the multidisciplinary treatment of DPN patients. Study purpose – study of efficiency of DPN patients management using a multidisciplinary approach. Patients and methods. The study included 50 patients (29 women and 21 men) aged 20 to 78 years (mean age = 57.6 ± 10.2 years) with diabetes mellitus (DM) of type 1 and 2 and DPN. All patients received multidisciplinary treatment consisting of pharmacotherapy, educational programs, KPT. All patients by Cocarnit (for 9 days). The observation period for the patients was 12 weeks. All the patients underwent assessment of neuropathic and asthenic symptoms. Results. Many patients were newly diagnosed with concomitant neurological (lumboischalgia, cervicalgia, tunnel syndromes, headaches, insomnia) and emotional (anxiety, depression) disorders. Authentically significant reduction in the average positive neuropathic and asthenic symptoms, improvement in average pain sensitivity was observed from Day 10 and persisted until 12 weeks of observation. Best value of effectiveness of interdisciplinary treatment was observed in patients with Stage 2 DPN. Conclusion. There is a low level of diagnostics of combined neurological and emotional disorders in patients with diabetes and DPN. The multidisciplinary treatment allows relatively quickly and firmly to reduce the severity of neuropathic and asthenic symptoms in DPN patients, most effectively – at the Stage 2A of DPN. The use of Cocarnit is effective and safe in complex therapy of DPN patients.